Chapter Introduction Rethinking Martyrdom - Fruchtman, Diane (Taylor & Francis, 2023)
This chapter outlines the historical and historiographical inaccuracy of privileging definitions of martyrdom that center on death, and situates this argument within the current scholarly conversation. It establishes both the academic consensus that "real" martyrdom requires death and the record of living martyrs in Christian history that proves that consensus wrong: indeed, living martyrs persist as real objects of spiritual devotion and emulation across the span of Christian history, not just in late antiquity. I introduce the main players in the book (Prudentius [c. 348-413], Paulinus of Nola [353-431], and Augustine [354-430]), summarize the subsequent chapters, explicate my methodology (close readings informed by literary-historical context; a heuristic of tripartite witness; multiple means of assessing potential reception), and discuss various objections-including the existence of the category of confessors and the habits of mind and scholarship that have resulted in our failure to recognize living martyrs as martyrs, plain and simple.